The Effect of Small-Sided Games Training on the Passing Skills of Talagoray U18 Football School Players - Gema Lineker; Naluri Denay; Ardo Okilanda; Bram Sujadesman (Jurnal Master Penjas & Olahraga, 2026)
This study aimed to determine the effect of Small-Sided Games training on the passing ability of U-18 SSB Talagoray players. This research employed a quantitative pre-experimental method using a one-group pretest–posttest design. The participants consisted of 19 U-18 players selected using total sampling. Passing ability was measured using the Short Passing Test before and after 16 sessions of Small-Sided Games training. Data were analyzed using the Shapiro–Wilk normality test and a paired sample t-test with SPSS. The results showed that the mean passing score increased from 97.47 in the pretest to 111.42 in the posttest. Statistical analysis indicated a significant improvement after the intervention (p < 0.05), demonstrating that Small-Sided Games training effectively enhanced players' passing ability. It is concluded that Small-Sided Games can be recommended as an effective training method to improve passing performance among youth football players and support overall team performance.